Analysis of Machine Operator Work Posture Using the Rapid Entire Body Assessment (REBA) and Rapid Upper Limb Assessment (RULA) Methods at the Maintenance Workshop of PT. DONGGI SENORO LNG - Deskha Satriany Fergustyan Putra; Yuni Krida Sakti; Clora Widya Brilliana; Bambang Sutejo (ILTEK : Jurnal Teknologi, 2026)
This study analyzes the working posture of machine operators at PT. DONGGI SENORO LNG to evaluate ergonomic risk levels and their potential impact on health and productivity. Observations revealed postures ranging from low to moderate risk, particularly in tasks involving bending, twisting, or excessive reaching. Posture assessments were conducted using Rapid Entire Body Assessment (REBA) and Rapid Upper Limb Assessment (RULA). REBA scored 5 for the lower body, indicating medium risk requiring further investigation and potential modifications. RULA scores of 3–4 for the upper body indicated low risk but warranted preventive evaluation. The differing results between the two methods underscore the need for a comprehensive assessment of the entire body. Findings suggest potential musculoskeletal disorder (MSD) risks if corrective actions are not implemented. Recommended interventions include workplace modifications, assistive tools, job rotation, and posture training to enhance comfort, reduce injury risk, and support long-term productivity. Keywords: Working posture, REBA, RULA, ergonomics, machine operator.